Determinants of Islamic Banking Competitiveness in Indonesia, Malaysia, and Brunei Darussalam - Nurma Sari; Lutpi Sahal; Zaki Zaini; Asmak Binti Ab Rahman (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: Financial ratios play a crucial role in measuring the performance and competitive position of Islamic banking institutions. Indicators such as profitability, operational efficiency, asset quality, and liquidity reflect the ability of banks to sustain growth and maintain a competitive edge. Accordingly, this study investigates the factors affecting the competitiveness of Islamic banks across Indonesia, Malaysia, and Brunei Darussalam. Method: This competitiveness is measured using Islamic bank assets as the dependent variable, and net profit, ROA, ROE, CAR, and CIR as the independent variables. A quantitative descriptive research approach using panel data regression was used to determine the effect of Islamic bank profitability on competitiveness in peer countries. Data were collected through secondary data from all Islamic banks in peer countries (Indonesia, Malaysia, and Brunei Darussalam) from 2022 to 2025. Result: The results indicate that net profit, ROE, and ROA significantly enhance the competitiveness of Islamic banks, while CIR and CAR show no significant effect. This finding highlights the critical role of profitability-related indicators in driving competitive performance. In contrast, operational efficiency and capital adequacy appear to have a more limited contribution within the observed banking systems. Implication: This study demonstrates that profitability-based measures are more effective drivers of competitiveness than capital adequacy and cost-efficiency indicators. The results offer practical insights for policymakers and banking practitioners seeking to strengthen the resilience and market position of Islamic banks in the region. Originality or Novelty: The novelty of this study lies in its use of Islamic bank assets as a measure of competitiveness and its comparative analysis across three countries with well-developed Islamic banking sectors—Indonesia, Malaysia, and Brunei Darussalam. By applying panel data regression to cross-country banking data, this study extends existing research beyond single-country investigations. It provides new evidence on the determinants of competitiveness in Islamic banking